BIOM-61. SYSTEMATIC REVIEW OF BIOLOGIC CORRELATES OF FRAILTY IN SOLID TUMORS: IMPLICATIONS FOR BRAIN TUMORS. (14th November 2022) - Sass, Dilorom (Delia); Streck, Brennan; Cooper, Diane; Guida, Jennifer; Armstrong, Terri
Abstract: BACKGROUND: Cancer and cancer treatments contribute to accelerated aging and frailty, which is present in over 50% of adult cancer survivors and increases vulnerability to poor outcomes. Biomarkers of frailty would allow for early identification and timely interventions. The purpose of this review is to synthesize the current literature examining biomarkers of frailty across solid tumor patients, including primary brain tumors (PBT). METHODS: The systematic review was conducted using preferred reporting items for systematic reviews and meta-analysis (PRISMA) guidelines. PubMed, Web of Science, and Embase, were searched by the medical librarian (D.C.) of all reports from the inception to December 08, 2021. Inclusion criteria were: a) English language, b) biomarkers of aging hallmarks, c) association between biomarkers and frailty. Studies were limited to human solid tumors. Two reviewers (D.S. and B.P.S.) independently screened titles, abstracts, and full-text articles using Covidence platform with conflict resolution by the third researcher (T.S.A.). Included studies were independently evaluated for quality assessment using NIH tools for Observational Cohort, Cross-Sectional and Case-Control studies. RESULTS: In total, 915 reports were screened and 15 full-text articles were included for the review. Studies were most commonly in breast tumors with no PBTs identified. Most were cross-sectional using small sample sizes. Fried, Balducci, and Leuven Oncogeriatric Frailty tools and cytokines (i.e. Interleukin-6 and C-reactive protein) were commonly used. Increased inflammatory response was the prevalent identified mechanism. Threats to internal validity of the studies were the use of unvalidated cut-off scores or modification of existing tools in about 50% of studies. Only six studies were rated as good using quality assessment ratings. CONCLUSIONS: Varied use of frailty measures and nonspecific blood biomarkers limited conclusions for mechanisms of frailty in cancer survivors. There are missed opportunities in neuro-oncology; inclusion of frailty assessment and biomarkers is instrumental to advancing science in PBTs.